Glucose Production with Crude Cellulose Corn Stover Substrate Using Cellulase Enzymes from Isolate B2S8 - Sinaga, Rendy; Gunam, Ida Bagus Wayan; Antara, Nyoman Semadi (Metamorfosa: Journal of Biological Sciences, 2022)
The aim of this study is to determine the crude cellulose corn stover substrate concentration and saccharification time to produce high glucose. Cellulose contained in the corn stover has potential converted into glucose by enzymatic hydrolysis using cellulase enzymes. Glucose production in different substrate concentrations and saccharification times uses a factorial randomized block design (RBD) consisting of two factors. The first factor is the substrate concentration which consists of 4 levels, namely 2%, 3%, 4%, and 5% (w/v). The second factor is the saccharification time which consists of 4 levels, namely 24 hours, 48 hours, 72 hours, and 96 hours. The observed variables include glucose level, cellulose residue, pH, and total dissolved solid. The results showed that 5% substrate concentration and 96 hours saccharification time was the best treatment for producing the maximum glucose level was 0,3003 mg/mL, the minimum cellulose residue after saccharification was 17,75%, pH after saccharification was 6,1, and the highest total dissolved solid after saccharification was 2,7°Brix.